1993
DOI: 10.1128/mcb.13.3.1746
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the stage-specific embryonic enhancer-binding protein SSAP-1.

Abstract: We have demonstrated that a highly conserved segment of DNA between positions -288 and -317 (upstream sequence element IV [USE IV]) is largely responsible for the transcriptional activation of the sea urchin H1-1 histone gene during the blastula stage of embryogenesis. This sequence is capable of acting as an embryonic enhancer element, activating target genes in a stage-specific manner. Nuclear extracts prepared from developmentally-staged organisms before and after the gene is activated all contain a factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Threonine phosphorylation in the GQ domain mediates homodimerization of SSAP at mid-blastula stage of embryogenesis. Gel mobility-shift assays and Superose 12 gel filtration chromatography showed that SSAP is a 41-kDa species early in embryogenesis and changes to an 80-to ϳ100-kDa species coincident with the activation of late H1 gene transcription (12,13). However, no additional proteins were copurified with SSAP through protein-protein interaction, as determined by either affinity chromatography or immunoprecipitation under nondenaturing conditions (12, 14a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Threonine phosphorylation in the GQ domain mediates homodimerization of SSAP at mid-blastula stage of embryogenesis. Gel mobility-shift assays and Superose 12 gel filtration chromatography showed that SSAP is a 41-kDa species early in embryogenesis and changes to an 80-to ϳ100-kDa species coincident with the activation of late H1 gene transcription (12,13). However, no additional proteins were copurified with SSAP through protein-protein interaction, as determined by either affinity chromatography or immunoprecipitation under nondenaturing conditions (12, 14a).…”
Section: Resultsmentioning
confidence: 99%
“…Most of them have temporal profiles of expression that resemble those of their target genes, suggesting that genes encoding those transcription factors are themselves under the control of temporal regulatory mechanisms. Immunoblot analysis demonstrated that SSAPs are present in the sea urchin throughout embryogenesis (13). Microinjection experiments indicated that SSAP can transactivate the late H1 gene promoter through the USE IV enhancer sequence beginning at the mid-blastula stage even though its DNA binding activity is present in the embryos at earlier stages (12,13).…”
mentioning
confidence: 99%
See 3 more Smart Citations